2013
DOI: 10.1111/1365-2745.12118
|View full text |Cite
|
Sign up to set email alerts
|

The lanky and the corky: fire‐escape strategies in savanna woody species

Abstract: Summary1. Fire and herbivory are the main disturbances shaping the structure of savannas. In these ecosystems, the key strategies by which woody plants escape fire are either early height growth (the lanky strategy) or early bark growth (the corky strategy). We hypothesize that the dominance of each strategy in different savannas depends on the prevailing disturbance regimes. Given the importance of herbivory in afrotropical savanna, we expect woody plants in these savannas to be taller and have thinner barks … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
135
0
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(145 citation statements)
references
References 64 publications
5
135
0
5
Order By: Relevance
“…By contrast, the findings of our study indicated that bark thickness and stem diameter were the principal predictors of the type of resprouting, and that the inclusion of tree height in the analysis did not increase its predictive power. Similar findings have been obtained in comparative studies of the fire survival strategies of the vegetation of African and South American savannas (Dantas & Pausas 2013;Pausas 2014). Lawes & Clarke (2011) for example, showed that tree survival was correlated exclusively with bark thickness, rather than stem height or diameter.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…By contrast, the findings of our study indicated that bark thickness and stem diameter were the principal predictors of the type of resprouting, and that the inclusion of tree height in the analysis did not increase its predictive power. Similar findings have been obtained in comparative studies of the fire survival strategies of the vegetation of African and South American savannas (Dantas & Pausas 2013;Pausas 2014). Lawes & Clarke (2011) for example, showed that tree survival was correlated exclusively with bark thickness, rather than stem height or diameter.…”
Section: Discussionsupporting
confidence: 80%
“…Bark thickness was the most important factor, as observed in previous studies, which indicate that savanna vegetation impacted frequently by fires tends to select species with thicker bark (Dantas & Pausas 2013). The thickness of the bark determines its capacity for thermal insulation, which protects vital stem tissues from flames and high temperatures (Hoffmann & Solbrig 2003;Miranda & Sato 2005;Pausas 2014).…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…Fire has been occurring in the Brazilian savannas (Cerrado) for 10 million years (Simon et al 2009;Simon & Pennington 2012) and many Cerrado trees have survived fi res because of traits such as thicker bark (Dantas & Pausas 2013) which protects stems from high fi re temperatures and prevent topkill, or deciduous leaves that are less vulnerable to fi re or herbivory damage (Lucena et al 2015). Among Cerrado woody plants, the main consequences of burning are partial to complete loss of aerial biomass and, in more severe cases, plant death (Coutinho 1982;Hoff mann 1998;Hoff mann & Solbrig 2003;Hayashi & Appezzato-da-Glória 2007;Hoff mann et al 2009).…”
Section: Introductionmentioning
confidence: 99%